Potato late blight caused by Phytophthora infestans: From molecular interactions to integrated management strategies - Suo-meng DONG; Shao-qun ZHOU (Journal of Integrative Agriculture)
Over 170 years after the infamous Irish Potato Famine, potato late blight (PLB) caused by Phytophthora infestans remains the single most devastating disease of global potato production, causing up to 10 billion USD in yield loss and management costs. Through decades of research, growers and agronomists in the field as well as laboratory scientists have made significant progress in understanding the molecular pathogenesis process of this critical pathosystem and effective management strategies to control PLB. Yet, the need to feed an ever-increasing global population under changing climate demands continued improvement in efficient and sustainable PLB management schemes that can be implemented across a broad economic spectrum. In this review, we briefly summarize the current understanding of the molecular interaction between P. infestans and its host plants, highlight the current integrated pest management strategy to control PLB on local and continental scales, and discuss the potential of further improvement of sustainable PLB control through genetic enhancement of crop resistance and emerging crop protection technologies.